The tax implications of raising fees from the perspective of the borrower - Chohan, Taahirah (My University, 2015)
Cannot copy abstract
Thesis (M.Com. (Taxation))--University of the Witwatersrand, Faculty of Commerce, Law and Management, School of Accountancy, 2015.